Grey Game Model for Energy Conservation Strategies - Si-Huan Li; Wei-Guo Zhang; Lian-Sheng Tang (Journal of Applied Mathematics)
A grey game model is constructed for enterprise carbon emissions reduction and government policies on energy conservation, which explains the interaction equilibrium strategies between government and enterprises with resource constraints. The MATLAB tools are used to simulate the game process, and the result shows that the optimal strategy is consistent with the operation result. Finally, macroscopic countermeasures and suggestions are proposed for government and enterprise.